Antigenicity comparison of SARS‐CoV‐2 Omicron sublineages with other variants contained multiple mutations in RBD. Issue 2 (9th April 2022) - Li, Qianqian; Zhang, Mengyi; Liang, Ziteng; Zhang, Li; Wu, Xi; Yang, Chaoying; An, Yimeng; Tong, Jincheng; Liu, Shuo; Li, Tao; Cui, Qianqian; Nie, Jianhui; et al.
Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) variants, particularly those with multiple mutations in receptor‐binding domain (RBD), pose a critical challenge to the efficacy of coronavirus disease 2019 (COVID‐19) vaccines and therapeutic neutralizing monoclonal antibodies (mAbs). Omicron sublineages BA.1, BA.2, BA.3, as well as the recent emergence of C.1.2, B.1.630, B.1.640.1, and B.1.640.2, have multiple mutations in RBD and may lead to severe neutralizing antibody evasion. It is urgent to evaluate the antigenic change of the above seven variants against mAbs and sera from guinea pigs immunized with variants of concern (VOCs) (Alpha, Beta, Gamma, Delta, Omicron) and variants of interest (VOIs) (Lambda, Mu) immunogens. Only seven out of the 24 mAbs showed no reduction in neutralizing activity against BA.1, BA.2, and BA.3. However, among these seven mAbs, the neutralization activity of XGv337 and XGv338 against C.1.2, B.1.630, B.1.640.1, and B.1.640.2 were decreased. Therefore, only five neutralizing mAbs showed no significant change against these seven variants. Using VOCs and VOIs as immunogens, we found that the antigenicity of variants could be divided into three clusters, and each cluster showed similar antigenicity to different immunogens. Among them, D614G, B.1.640.1, and B.1.630 formed a cluster, C.1.2 and B.1.640.2 formed a cluster, and BA.1, BA.2, and BA.3 formed a cluster. Abstract : A few mAbs showed strong and broad‐spectrum neutralizing activity against the tested variants. The antigenicity of Omicron sublineages was significantly different from other variants. The Omicron immunogen‐elicited antibody was not sensitive to other variants.